The Use of Supplementary Immunisation Activities to Improve Uptake of Current and Future Vaccines in Low-Income and Middle-Income Countries: A Systematic Review Protocol - Kagina, Benjamin M.; Wiysonge, Charles S.; Abdullahi, Leila H.; Uthman, Olalekan A.; Hussey, Gregory D. (BMJ open, 2014)
Immunisation coverage data in low-income and middle-income countries (LMICs) suggest that more strategies need to be implemented to achieve and sustain optimal vaccine uptake. Among possible strategies to improve immunisation coverage are supplementary immunisation activities (SIAs). We are therefore interested in conducting a systematic review to assess whether SIAs complement routine immunisation programmes to improve vaccination coverage and prevent disease outbreaks. Our systematic review will focus on studies conducted in LMICs. With the help of an information specialist, we will search for eligible studies in PubMed, Web of Science, Scopus, Africa-Wide, Cochrane Library, WHOLIS, CINAHL, PDQ-Evidence as well as reference lists of relevant publications. Additionally, we will contact relevant organisations such as WHO and GAVI. Two authors will independently extract data from eligible studies and independently assess risk of bias by assessing the adequacy of study characteristics. The primary meta-analysis will use random effects models due to expected interstudies heterogeneity. Dichotomous data will be analysed using relative risk and continuous data using weighted mean differences (or standardised mean differences), both with 95% CIs. The findings from this systematic review will be discussed in the context of strengthening routine childhood immunisation services, routine adolescent immunisation services and introduction of future vaccines against tuberculosis and HIV/AIDS.
Keywords: immunisation; low-income and middle-income countries; vaccination